Systematic Layout Planning and Analytical Hierarchy Process for Laboratory Layout Optimization: A Case Study of DESPRIN - Sihotang, Mergie; Jawak, Josua Boyke William (Faculty of Engineering and Technology, Sampoerna University, 2024)
The Product Design and Innovation Laboratory (DESPRIN) at Del Institute of Technology plays a crucial role in supporting innovation. Yet, its current layout struggles to meet its users' diverse and evolving needs. This study addresses the problem of inadequate spatial configuration, which hampers workflow efficiency, ergonomics, and the lab's overall capacity to accommodate various activities. To resolve this issue, a flexible layout is designed using the Systematic Layout Planning (SLP) method, emphasizing optimizing space utilization, workflow, and spatial adaptability. Data collected from literature reviews, interviews, statistical analyses, and anthropometric measurements inform the design process to enhance the lab’s quality and spatial efficiency. The Analytical Hierarchy Process (AHP) is employed to prioritize key layout design factors, identifying capacity as the most critical element (0.4930), followed by facilities (0.1688), accessibility (0.1414), security (0.1270), and environment (0.0708). The study results in 13 new layout configurations that can accommodate various activities within DESPRIN, providing a more dynamic and responsive user environment.